THE EFFECT OF COMFORT AND SERVICE QUALITY OF HIJRAH STORE BRANCH II ON CONSUMER LOYALTY IN LHOKSEUMAWE CITY - Nurul Alya Fahzila; Sufi; Agustinawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The number of e-commerce that sells a variety of fashion products at lower prices and the ease of access to shopping without leaving the house, encourages many consumers to flock to do online shopping. So that this results in many offline stores that cannot adapt to all digital losing consumers. In contrast to the Hijrah Store store in Lhokseumawe city, this store can still retain its customers by providing comfort and good service in accordance with product quality. This study aims to see how the influence of convenience and service quality on consumer loyalty at the Hijrah Store Branch II Lhokseumawe store. This study uses descriptive quantitative research methods using non probability sampling and obtained 100 respondents as a research sample obtained from the Slovin formula. The data analysis method used in this study is multiple linear regression analysis, instrument test, classical assumption test and hypothesis testing and the coefficient of determination with the help of the SPSS 26.0 software program. The results showed that partially the comfort and service quality variables had a positive and significant effect on customer loyalty. With a sig value for the convenience variable of (0.003 <0.05) and a service quality variable of (0.001<0.05). While simultaneously convenience and service quality have a significant effect on consumer loyalty with a significant value of (0.000 <0.05).